In search of an evolutionary edge: Trading with a few, more, or many - Oded Stark; Doris A. Behrens (University of Bonn, Center for Development Research (ZEF), 2010)
Consider a population of farmers who live around a lake. Each farmer engages in trade with his m adjacent neighbors, where m is termed the span of interaction. Trade is governed by a prisoner's dilemma rule of engagement. A farmer's payoff is the sum of the payoffs from the m prisoner's dilemma games played with his neighbors to the left, and with his neighbors to the right. When a farmer dies, his son takes over. The son who adheres to his father's span of interaction decides whether to cooperate or defect by considering the actions taken and the payoffs received by the most prosperous member of the group comprising his father and his father's m trading partners. Under a conventional structure of payoffs, it is shown that a large span of interaction is detrimental to the long-run coexistence of cooperation and defection, and conditions are provided under which the social outcome associated with the expansion of trade when individuals trade with a few is better than that when they trade with many. Under the stipulated conditions it is shown, by means of a static comparative analysis of the steady state configurations of the farmer population, that an expansion of the market can be beneficial in one context, detrimental in another. 2 m 2 m – – Wir betrachten eine Population von Farmern, die rings um einen See leben. Jeder Farmer betreibt mit seinen m nächsten Nachbarn Tauschhandel, wobei m als Interaktionsspanne bezeichnet wird. Der Handel folgt den Spielregeln eines Gefangenendilemmas. Das Einkommen eines Farmers ergibt sich als Summe der Auszahlungen der m einzelnen Spiele, die der Farmer mit seinen Nachbarn zur Linken und Nachbarn zur Rechten spielt. Stirbt ein Farmer, übernimmt sein Sohn die Farm. Der Sohn, der die Interaktionsspanne m des Vaters beibehält, entscheidet sich für oder gegen die Wahl der kooperativen Strategie, indem er das Verhalten des wohlhabendsten Farmers aus einer Gruppe von Vorfahren repliziert, die aus seinem Vater und dessen m Handelspartnern besteht. Für eine konventionelle Auszahlungsstruktur wird gezeigt, dass eine große Interaktionsspanne der nachhaltigen Koexistenz von kooperativem und nicht-kooperativem Verhalten abträglich ist. Weiters werden Bedingungen für die Auszahlungsstruktur dargelegt, unter denen das durch eine Ausweitung der Handelsbeziehungen generierte Pro-Kopf-Einkommen höher ist, wenn Individuen ursprünglich wenige Handelspartner hatten, als wenn Individuen ursprünglich sehr viele Handelspartner hatten. Somit wird bei entsprechender Auszahlungsstruktur mittels statisch komparativer Analyse der Gleichgewichtskonfiguration der Farmer-Population nachgewiesen, dass eine Markterweiterung in manchen Fällen vorteilhaft sein kann, in anderen aber nicht.
Keywords: 330; Landwirtschaft; Tausch; Nachbarschaft; Gefangenendilemma; Evolutionäre Spieltheorie; Theorie